Quaker carpetbagger: J. Williams Thorne, Underground Railroad host turned North Carolina politician - Longley, Maximilian (McFarland & Company, Inc., Publishers, 2020)
The Ecclesiastical Trial -- Born into a Cold World -- Let Truth and Error Grapple -- The Federal Invasion and the Progressive Friends -- Reform, Slave Raid, War -- Keystone Stater and Tar Heel -- Cast Out -- The Carpetbagger and the Carpet Will -- Returning Home -- Speaking His Mind -- Appendix I. Memorial Resolution on J. Williams Thorne Adopted by the Progressive Friends Meeting, Longwood, 1897 -- Appendix II. J. Williams Resorts to Satire to Defend What He Considers the Principles of a True Republic, 1877.